Analisis Skala Ekonomis Pada Industri Batu Bata di Desa Tulikup, Gianyar, Bali - Budiartha, I Kadek Agus; Trunajaya, I Gede (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 1, Februari 2013 (pp. 1-70))
This research aims were to determine the economic of scale and the nature of industry production of brick industry in Tulikup Vilage, Gianyar, Bali. The results of this study indicate that the economic of scale position was on the increasing returns to scale, it can be seen from the sum of the regression coefficients of labor and capital regression coefficient was greater than one. Meanwhile the nature of industry production was labor intensive, this condition indicated by the regression coefficient of labor that greater than the regression coefficient of capital.
Keywords: economic of scale , nature of industry production , increasing return to scale , labor intensive